ANTERIOR DECOMPRESSION, FUSION AND PLATING IN CERVICAL SPINE INJURY: OUR EARLY EXPERIENCE - Raja, Riaz A.; Makhdoom, Asadullah; Qureshi, Aftab Ahmed (Journal of Ayub Medical College Abbottabad, 2008)
Objective: To evaluate the efficacy of anterior cervical decompression, fusion and titanium plate fixation in sub axial cervical spine injuries in respect of neurological outcome, postoperative stability and early rehabilitation. The Descriptive case series study was conducted at Department of Neurosurgery, Liaquat University Hospital, Jamshoro, Sindh Pakistan during year 2005 to 2007. Methods: Patients with cervical spine injuries were admitted during study period were included in this study. All cases were evaluated for their clinical features. During initial phase, level and degree of neurological injury was assessed using ASIA impairment scale. Cervical traction was applied to all patients. Operative and post operative record with x-rays and MRI were maintained. Patients with Injury to C3-6 underwent decompression, fusion and local titanium plate implant fixation by anterior approach. The follow-up ranged from 6 to 12 months with clinical and radiological assessment. Results: 37 cases of sub axial cervical spine injuries included in this study during year 2005 to 2007. Out of these, 28 (75.67%) were males and 9 (24.32%) females. Age range was 8-60 years mean (32-40%). Common mode of injury was fall. Post operative follow up showed good clinical and radiological outcome, bony fusion and favour early rehabilitation. No immediate complication found except temporary dysphagia. Conclusion: Anterior decompression, fusion and titanium plate fixation is an effective method with good neurological and radiological outcome. Keywords: Cervical spine injury, anterior cervical decompression